Massage - Thomas, Sara; Translated by Anees Ahmad (Karachi Fareed Publisher, 2014)
Offering guidance for relief from disorders in every part of the body, this book provides comprehensive step-by-step instructions and illustrations. It includes detailed instructions on treating specific ailments. This book transforms the ancient art of touch into a precise healing skill.
Include Illustrations
Keywords: Massage -- Bunyadi Astrok -- Mukamal Jismani Massage